2013
DOI: 10.2174/1874431101307010001
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Storage Healthcare — The Basis of a Planet-Wide Public Health Care Network

Abstract: Background:As health providers move towards higher levels of information technology (IT) integration, they become increasingly dependent on the availability of the electronic health record (EHR). Current solutions of individually managed storage by each healthcare provider focus on efforts to ensure data security, availability and redundancy. Such models, however, scale poorly to a future of a planet-wide public health-care network (PWPHN). Our aim was to review the research literature on distributed storage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While this would not impede medical treatment, nor cost a hospital anything in ransom money, it nevertheless constitutes a serious breach of privacy. 11 And there could be little done to stop a hacker from using the information they have gained from blackmailing particularly vulnerable patients in a more traditional way.…”
Section: Caveatsmentioning
confidence: 99%
“…While this would not impede medical treatment, nor cost a hospital anything in ransom money, it nevertheless constitutes a serious breach of privacy. 11 And there could be little done to stop a hacker from using the information they have gained from blackmailing particularly vulnerable patients in a more traditional way.…”
Section: Caveatsmentioning
confidence: 99%
“…It has been concluded that it is feasible for a distributed healthcare network to scale to provide planet-wide care (Kakouros, 2013). The socio-economic feasibility has not been demonstrated yet; there are very few precedents of using distributed networks in healthcare.…”
Section: Distributedmentioning
confidence: 99%
“…It has been concluded that it is feasible for a distributed healthcare network to scale to provide planet-wide care (Kakouros, 2013). The socio-economic feasibility has not been demonstrated yet; there are very few precedents of using distributed networks in healthcare.…”
Section: Distributedmentioning
confidence: 99%